Trends of using social media for the green labelling of modern mobile phones - Sewar Alkhatib; Veronika Keller; Petra Kecskés (Cogent Business & Management, 2024)
This study explores contemporary practices by three major companies, Samsung, Apple and Huawei, to promote the environmentally friendly attributes of mobile phones by utilizing social media platforms. The research employs a combination of literature review and data analysis to investigate the strategies used by these companies in advertising their environmental initiatives on popular social media platforms such as Facebook, Instagram, YouTube and Twitter. The findings underscore the increasing significance of social media in the realm of green labelling initiatives. The study reveals the potential of social media to enhance customer awareness and influence purchasing behaviour in the dynamic mobile phone sector. The article recommends further research in this domain to guide manufacturers in formulating effective strategies amid the evolving landscape of the mobile phone industry.
Keywords: 650; green marketing; sustainability; digital marketing; green products; social media